2019
DOI: 10.1111/cas.14082
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of the LacdiNAc‐glycosylated prostate‐specific antigen assay for prostate cancer detection

Abstract: To reduce unnecessary prostate biopsies (Pbx), better discrimination is needed. To identify clinically significant prostate cancer (CSPC) we determined the performance of LacdiNAc‐glycosylated prostate‐specific antigen (LDN‐PSA) and LDN‐PSA normalized by prostate volume (LDN‐PSAD). We retrospectively measured LDN‐PSA, total PSA (tPSA), and free PSA/tPSA (F/T PSA) values in 718 men who underwent a Pbx in 3 academic urology clinics in Japan and Canada (Pbx cohort) and in 174 PC patients who subsequently underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
0
17
1
Order By: Relevance
“…Involvement of PIP in immunoregulation was described in cancer and also suggested contribution to seminal plasma immunosuppresive properties [ 71 , 72 ]. Many recent reports point to the presence of an antigen called lacdiNAc (GalNAcβ1-4GlcNAc) in glycans of a KLK3 in the context of neoplastic transformation [ 73 , 74 , 75 , 76 , 77 ]. The occurrence of the above mentioned structures may be also considered in LTF.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of PIP in immunoregulation was described in cancer and also suggested contribution to seminal plasma immunosuppresive properties [ 71 , 72 ]. Many recent reports point to the presence of an antigen called lacdiNAc (GalNAcβ1-4GlcNAc) in glycans of a KLK3 in the context of neoplastic transformation [ 73 , 74 , 75 , 76 , 77 ]. The occurrence of the above mentioned structures may be also considered in LTF.…”
Section: Discussionmentioning
confidence: 99%
“…In the cohort of prostate biopsy patients LDN-PSAD demonstrated significantly higher clinical performance to discriminate CSPC compared with LDN-PSA, PSAD, total PSA and free/total PSA ratio. The authors concluded that LacdiNAc-glycosylated PSA is significantly more efficient than the conventional PSA test in identifying patients with CSPC [111].…”
Section: Lacdinac Structuresmentioning
confidence: 99%
“…LDN and LN were purchased from Carbosynth (OA44637 and OA08244, respectively). The 1 H-NMR resonances of LDN and LN (α/ β mixture) were completely assigned through standard 2D-TOCSY (30 and 60 ms mixing time), 2D-ROESY/2D-NOESY (500 ms mixing time) and 2D 1 H, 13 C-HSQC experiments at 298 K. Typical concentrations were 1 mM for the heteronuclear experiments in D 2 O Tris (D11)-DCl buffer solutions with pD 7.5. The resonance of 2,2,3,3tetradeutero-3-trimethylsilylpropionic acid (TSP) was used as a chemical shift reference in the 1 H-NMR experiments (δ TSP = 0 ppm).…”
Section: Nmr Assignment Of Ldn and Lnmentioning
confidence: 99%
“…[8] Additionally, LDN is a well-established cancer biomarker overexpressed on glycoproteins associated with several human cancers, including colon, pancreas, ovarian and prostate cancers. [9][10][11][12][13] From the recognition point of view, two human lectins, galectin-3 (hGal-3) and the macrophage galactose C-type lectin (hMGL) have previously been identified to recognize LDN epitopes. [14][15][16] In fact, either hGal-3 and hMGL were previously associated to molecular pathways that may contribute to pathogen infection [17][18][19][20] or tumour evasion of the immune system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation